"Жангар" туулийн хэл найруулгын зарим онцлог - Ван Мандуга (Mongolian Studies, 2023)
"Jangar" epic is one of the most valuable works of art of the Mongolian people. The main reason came down from the century to centuries of “Jangar” epic is the features of literary language and role description. The distinctive feature of the "Jangar" epithet is its main reason for centuries. In addition, it is a valuable work in the history of the Mongols as well as the many distinctive features of society, nomadic culture and economy. The literary language has played an important role in literary content and art description. It shows that the literary language of "Jangar" epic is more important than the main content. The importance of language is directly related to the communication of the verb. Therefore, it is required to conduct essential research on the literary language of “Jangar” epic based on the purpose of listening to "Jangar" epic.